2021
DOI: 10.3389/fcell.2021.631428
|View full text |Cite
|
Sign up to set email alerts
|

OTUD5 Variants Associated With X-Linked Intellectual Disability and Congenital Malformation

Abstract: BackgroundX-linked intellectual disability (XLID), which occurs predominantly in males, is a relatively common and genetically heterogeneous disorder in which over 100 mutated genes have been reported. The OTUD5 gene at Xp11.23 encodes ovarian tumor deubiquitinase 5 protein, which is a deubiquitinating enzyme member of the ovarian tumor family. LINKage-specific-deubiquitylation-deficiency-induced embryonic defects (LINKED) syndrome, arising from pathogenic OTUD5 variants, was recently reported as a new XLID wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In fact, life expectancy in LINKED syndrome may be longer than previously thought. Saida et al described three patients with in vivo OTUD5 missense variants associated with LINKED syndrome [ 93 ]. They identified three males with X-linked intellectual disability (XLID) in two families with developmental delay.…”
Section: Otud5-related Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, life expectancy in LINKED syndrome may be longer than previously thought. Saida et al described three patients with in vivo OTUD5 missense variants associated with LINKED syndrome [ 93 ]. They identified three males with X-linked intellectual disability (XLID) in two families with developmental delay.…”
Section: Otud5-related Diseasesmentioning
confidence: 99%
“…These included a pair of adult siblings with a novel missense OTUD5 variant. They had a relatively mild phenotype, showed no cardiac or urogenital malformations and lived into their 40s [ 93 ]. The p.Arg404Trp variant was previously reported by Beck et al to be a lethal variant of OTUD5 with a typical LINKED syndrome phenotype [ 86 ].…”
Section: Otud5-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beck et al (2021) independently reported 10 pediatric cases from seven different families with an OTUD5 pathogenic variant and named this disease LINKED syndrome. Saida et al (2021) also described three affected males in two families. These two cohort studies included patients with lifespans from neonatal death to the greatest age of 40 years, suggesting that the phenotype caused by OTUD5 genetic variation is more extensive than previously thought (Saida et al, 2021).…”
mentioning
confidence: 92%
“…The OTUD5 (OTU domain‐containing protein 5) gene (MIM# 300713) at Xp11.23 encodes the protein ovarian tumor (OTU) deubiquitinase 5 (Yin et al., 2019), a K48/K63 linkage‐specific deubiquitinating enzyme (DUB) of the OTU family (Mevissen et al., 2013). The OTUD5 gene was previously suggested as a candidate gene for ID according to screening of three large cohorts of patients (Beck et al., 2021; Saida et al., 2021; Tripolszki et al., 2021). Twenty‐six patients with clinical symptoms of XLID have been described in three large cohort studies, with nine variants identified in the OTUD5 gene.…”
Section: Introductionmentioning
confidence: 99%